2022
DOI: 10.1007/s11409-022-09322-x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of metacognitive skills in self-regulated learning: effects on strategy application and content knowledge acquisition

Abstract: Metacognitive skills are often considered domain-general, therefore they have the potential to transfer across domains, subjects, and tasks. However, transfer of metacognitive skills seldomly occurs spontaneously. Schuster et al., (2020) showed that training can have beneficial effects on spontaneous near and far transfer of metacognitive skills. However, evidence of metacognitive skill transfer resulting in superior acquisition of content knowledge is pending. In the present study we set out to extend prior f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
0
12
0
2
Order By: Relevance
“…This is because students’ organizational abilities will be better. As stated by Stebner et al, by fostering self-regulated learning, the students will be increasingly able to organize their learning consciously [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because students’ organizational abilities will be better. As stated by Stebner et al, by fostering self-regulated learning, the students will be increasingly able to organize their learning consciously [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…They occupy a decisive role in facilitating the process of foreign language learning insofar as they can be transferred by learners across a myriad of learning tasks (e.g., reading, listening, speaking, writing, vocabulary tasks) in a specific language rather than across languages (i.e., Arabic, English, French, Spanish, German, Russian, Amazigh). This was buttressed by prior scholarly research revealing that metacognitive skills and strategies are transferred to many learning scenarios and domains (Stebner, 2022). Further, many researchers (e.g., Ping & Luan, 2017;Ranjan, et al, 2019;Waldvogel, 2013;Wenden, 1998) put forth that language proficiency is a determinant factor for effective learning strategy use.…”
Section: Language Learning Strategies (Llss): a Brief Overviewmentioning
confidence: 99%
“…Much scholarly research underscores the importance of LSs in enhancing second language learning (e.g., Cohen, 1998;O'Malley, et al, 1985;Oktoma, et al, 2020;Oxford, 1990;Ranjan, et al, 2019;Schuster, et al, 2023;Stebner, et al, 2022). Actually, strategies related to learning serve as "a resource that learners can turn to in solving language learning tasks" (Takač, 2008, pp.50-51).…”
Section: Introductionmentioning
confidence: 99%
“…Four articles addressed self-regulated learning. In an intervention study, Stebner et al (2022) demonstrated how hybrid training of cognitive and metacognitive skills facilitates near transfer and to some extent far transfer of metacognitive skills. Eshuis et al (2022) reported an intervention study of self-directed learning in which students were engaged in technical problems and asked to create concept maps of their acquired knowledge.…”
Section: Contributionsmentioning
confidence: 99%